Retratos de mujeres salvajes en la ficción de Pilar Pedraza - Valeria Palmieri (Confluenze, 2017)
When the narrative converges with a world of monstrosity, the speaking subject and the object described would establish a dichotomous relation, consisting on words and silences that determine who has the right to speak clearly and who is going to be the subject of discussion. Historically, writers have silenced women throughout literary narrative, regarding them as an instrument to project the conjectures of the patriarchal society. The misogynistic mythology described them as a constant threat to social order, giving a bequest of controversial characters still included in the fiction of modern authors. Analysing the protagonists of select novels by Pilar Pedraza, a rewriting of their portrayals could be heightened, as the perspective of the descriptions of these terrible figures changes when a woman is the one to create fantastical narration.